Investigating the impact of changes in iteration-likelihoods on design process performance. (September 2015) - Shapiro, Daniel; Hamraz, Bahram; Sommer, Anita F; Clarkson, P John
Research on changes in design has mainly focused on the product domain, which is the manifestation of the design process. This article investigates changes in the process domain, which describes the execution of coordinated and concurrent design activities through interdisciplinary teams. More specifically, this article focuses on changes in the iterative behavior of activities as one of the key levers determining the performance of complex concurrent design processes. In activity network–based models of design processes, the occurrence of such behavior is often expressed probabilistically through iteration-likelihoods. First, the impact of iteration-likelihood changes on the effort and duration of both individual activities and the overall design process is examined through stochastic analysis. Consequently, a method for the investigation of such changes is developed, which grounds on an experimental approach using Monte Carlo simulation of activity network–based process models. The method is applied to the design process of a high-speed machining device for the manufacturing of planetary-ball-bearing housings. This analysis results in a two-dimensional criticality ranking of potential iteration-likelihood changes and in the identification of the most affected individual activities. The article concludes with managerial implications for process planning and improvement and discusses which design activities need to be targeted by project management to prevent and react to critical iteration-likelihood changes.